Validation of high performance liquid chromatographic and spectrophotometric methods for the determination of the antiparkinson agent pramipexole dihydrochloride monohydrate in pharmaceutical products - Serpil Sevim; Nevin Erk (Universidade de São Paulo, 2015)
abstract The antiparkinson agent pramipexole dihydrochloride monohydrate was quantified in pharmaceutical products by high performance liquid chromatography (HPLC) and derivative spectrophotometry. The first method was based on HPLC using tamsulosin HCl as an internal standard. In this method, chromatographic separation was achieved using a LiChrospher 60 RP column at 25°C, with a flow rate of 1.0 mL/min at 263 nm. The eluent comprised 0.01 mol/L ammonium acetate (pH 4.4) and acetonitrile (35:65 by volume). The linearity range was found to be 10.0-30.0 µg/mL with a mean recovery of 100.5 ± 1.10. The limit of detection (8 ng/mL) and limit of quantification (50 ng/mL) were calculated. In the second method, the first derivative spectrophotometric technique for the determination of pramipexole dihydrochloride monohydrate was performed by measuring the amplitude at 249 and 280 nm. In the first derivative technique, the absorbance and concentration plot was rectilinear over the 5.0-35.0 µg/mL range with a lower detection limit of 1.5 ng/mL and quantification limit of 4.5 ng/mL. The typical excipients included in the pharmaceutical product do not interfere with the selectivity of either method. The developed methods were validated for robustness, selectivity, specificity, linearity, precision, and accuracy as per the ICH and FDA guidelines (ICH Q2B, 1996; FDA,2000). In conclusion, the developed methods were successful in determining the quantity of the antiparkinson agent pramipexole dihydrochloride monohydrate in pharmaceutical products. The RSD values for the pharmaceutical product used in this study were found to be 0.97% for the HPLC method and 0.00% for the first derivative spectrophotometric method.